1999
DOI: 10.1002/j.1550-8528.1999.tb00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y Expression and Endogenous Leptin Concentrations in a Dietary Model of Obesity

Abstract: LAUTERIO, THOMAS J., MICHAEL J. DAVIES, MARK DEANGELO, MICHAEL PEYSER, AND JAMES LEE. Neuropeptide Y expression and endogenous leptin concentrations in a dietary model of obesity. Obes Res. 1999;7: 498-505. Objective: To determine how leptin concentrations and neuropeptide (NPY) are regulated in a model of dietary obesity in relation to relative growth (RG) and relative food consumption (RFC). Research Methods and Procedures: Sprague-Dawley rats were fed a moderately high-fat diet for 14 weeks over which time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
6
21
0
Order By: Relevance
“…In accordance with previous data, 29 in OP rats after 12 weeks on the diet, plasma insulin was increased Ϸ2-fold compared with that in OR rats (Table). As expected, pioglitazone prevented the elevation in plasma insulin in OP rats (Table).…”
Section: Body Weight Circulating Insulin and Sodium Excretion In Opsupporting
confidence: 92%
“…In accordance with previous data, 29 in OP rats after 12 weeks on the diet, plasma insulin was increased Ϸ2-fold compared with that in OR rats (Table). As expected, pioglitazone prevented the elevation in plasma insulin in OP rats (Table).…”
Section: Body Weight Circulating Insulin and Sodium Excretion In Opsupporting
confidence: 92%
“…Another possible explanation for the earlier increase in BP in OP rats on a high-salt diet may be related to the pressor effect of leptin, as recently reported (23). Our own data or data reported by others (29) indicate that OP rats are hyperleptinemic by the end of the diet. Data showed that high-salt diets induced a significant 40% increase in plasma leptin in OP rats.…”
Section: Discussionsupporting
confidence: 72%
“…Leptin can generate oxidative stress, as has been reported for endothelial cells in culture. 45 In addition, leptin indirectly stimulates production of inflammatory cytokines such as interleukin-6 and tumor necrosis factor-␣, which increase NADPH oxidase production. 9 However, no data suggest that leptin stimulates ROS generation in the brain.…”
Section: Discussionmentioning
confidence: 99%